Núcleo de Oficinas e Trabalho: estudo de caso sobre uma tecnologia social e a promoção do Bem Viver - Rodrigues, Kátia Liane (Universidade Federal de São Carlos, 2020)
Social inclusion through work, in the area of mental health, presents itself as a field of research endowed with challenges, as it transcends discussions in health. The debate about the right to work, work with social and affective value points to discussions that have a possible encounter with social technologies in the area of science and technology. The projects that develop work and income generation activities, inspired by the solidarity economy, use associative and cooperative strategies to organize the way the groups work, developing true replicable social technologies. Considering that social cooperativism is a strategy of social inclusion through work for people in social and economic disadvantage, this doctoral thesis aims to analyze the experience of a social technology, in terms of promoting social inclusion through the work and production of Good Living, from the perspective of its participants. This is a case study carried out at the Center for Workshops and Work (NOT), located in the city of Campinas / SP. NOT is one of the psychosocial rehabilitation projects of the Dr. Cândido Ferreira Health Service (SSCF) and aims to offer work and income generation activities to three hundred people in the municipal health network. The research with a qualitative approach, had a semi-structured interview script that was built from the considerations of the Application Manual of the Functionality Classification Table for Mental Health. Ten interviews were conducted, with the criterion of being included in a workshop for at least one hundred and eighty days. The results made it possible to characterize the participants of the research and social technology, with regard to gender, age group, education and time of inclusion in the service. To collect data regarding treatment, such as: place, time and intensity of care, use of medication and type of illness. And also to identify social aspects such as: housing situation and receiving benefits. Through semi-structured questions, it was possible to understand the history and life projects of the participants and thereby analyze the potential of TS-NOT as a promoter of social inclusion through work. The results of the research indicated that the inclusion in work workshops and income generation, within the scope of the production of new meanings of life, promotion of self-care and new sociability, can provide practices of Good Living.
Center for Workshops and Work: a case study on social technology and the promotion of Good Living
Keywords: Tecnologia social; Economia solidária; Saúde mental; Bem viver; Inclusão social pelo trabalho; Social technology; Solidarity economy; Mental health; Good living; Social inclusion through work; CIENCIAS SOCIAIS APLICADAS